Reflective Practice on Nursing Students: A Qualitative Study - Azizah Khoiriyati; Novita Kurnia Sari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: The gap between theory and practice in clinical education settings is still common. Reflective practice in students of a profession program emphasizes the theoretical knowledge that has been acquired and the clinical experience. The purpose of this research was to explore the experience of reflective practice among the students of the Nursing Profession Program. Methods: A qualitative study design was undertaken. Focus group discussions were conducted with 16 participants divided into two groups using Zoom virtual meeting application. Instrument used semi-structured interview guidelines and data analysis used thematic analysis. Results: This research resulted in four themes, namely the gap between theory and practice; the benefits of reflective learning; experiences and expectations; and some barriers and challenges to reflective practice. Conclusion: Based on the existing results, it can be concluded that, although there are still some barriers in its implementation, the implication of this study can facilitate students of profession programs in overcoming the gaps between theories and practical experience during professional education.